Prevalence of and factors associated with long COVID among US adults: a nationwide survey - Juanjuan Shi; Rui Lu; Yan Tian; Fengping Wu; Xiaozhen Geng; Song Zhai; Xiaoli Jia; Shuangsuo Dang; Wenjun Wang (BMC Public Health)
Abstract Background People with long COVID report prolonged, multisystem involvement and significant disability. This study aimed to determine long COVID prevalence and factors associated with it among US adults using nationally representative data. Methods This cross-sectional analysis utilized data from 2022 Behavioral Risk Factor Surveillance System survey, a nationally representative telephone survey conducted among noninstitutionalized adults aged ≥ 18 years residing in the United States. Age-adjusted prevalence of long COVID was calculated using weighted survey analysis. Poisson regression was employed to assess adjusted prevalence ratios (aPRs) associated with long COVID across various demographic, socioeconomic and health-related characteristics. Results Among 390,233 participants, 120,178 reported COVID-19, with 25,582 experiencing long COVID. Age-adjusted prevalence of self-reported COVID-19 and long COVID were estimated at 34.1% (95% CI, 33.7–34.4%) and 7.2% (95% CI, 7.0–7.4%) as of 2022, respectively. Among adults reporting COVID-19, 20.9% (95% CI, 20.5–21.4%) had ever experienced long COVID. An inverted U-shaped association was observed between long COVID risk and age, with the highest prevalence (23.5%) in the 45–54 age group. Long COVID was more prevalent among women (aPR, 1.40 [95% CI, 1.34–1.47]), individuals without a spouse (aPR, 1.06 [95% CI, 1.00–1.13]), uninsured (aPR, 1.16 [95% CI, 1.06–1.27]), and those with a high school education (aPR, 1.17 [95% CI, 1.12–1.23]), cardiovascular disease (aPR, 1.17 [95% CI, 1.09–1.25]), depressive disorder (aPR, 1.41 [95% CI, 1.34–1.48]), chronic obstructive pulmonary disease (aPR, 1.33 [95% CI, 1.24–1.43]), asthma (aPR, 1.28 [95% CI, 1.21–1.35]), and kidney disease (aPR, 1.11 [95% CI, 1.01–1.21]). Long COVID was less prevalent among non-Hispanic Black (aPR, 0.87 [95% CI, 0.81–0.95]), students (aPR, 0.87 [95% CI, 0.76–0.99]) or retired individuals (aPR, 0.89 [95% CI, 0.82–0.98]), and those with household incomes ≥$100,000 (aPR, 0.85 [95% CI, 0.79–0.92]). Conclusions Long COVID affects 7.2% of US adults, with higher vulnerability among women, middle-aged individuals, White individuals, socioeconomically disadvantaged groups, and those with chronic conditions. These findings underscore the need for targeted public health strategies to address disparities in long COVID burden and support high-risk populations.